Tinjauan Yuridis Diperbolehkannya WNA Memiliki SHMSRS Berdasarkan UU CK Dan PP No. 18 Tahun 2021 - Natasha, Devri Valentina Frenska (Magister Kenotariatan Universitas Surabaya, 2024)
The Residence has a strategic role in shaping the personality and character of the nation and as a way to build a complete Indonesian society that is self-reliant, independent, and productive. Therefore, a residence in the residence the form of a residence needs to be fulfilled by every country in the form of a decent house and an affordable price. This fulfillment can be realized in the form of the construction of flats. Flats are not only intended for Indonesian citizens but also for foreigners. So that the problems discussed are the provisions of Ownership Rights on Flat Units for Foreign Citizens (WNA) in Indonesia based on Law no. 11/2020 and PP No. 18/2021. Ownership of flats can be marked by the existence of a Certificate of Ownership of Flat Units (SHMSRS). The ownership of flats for foreigners has limitations as regulated in, Law No. 11 of 2021, Government Regulation Number 103 of 2015 concerning Ownership of Residential Houses or Occupancy by Foreigners Domiciled in Indonesia, Ministerial Regulation ATR/ Ka.BPN No. 29 of 2016 concerning Procedures for Granting, Releasing, or Transfer of Rights to Ownership of Residential Houses or Occupancy by Foreigners Domiciled in Indonesia and Government Regulation Number 18 of 2021 concerning Management Rights, Land Rights, Flats Units, and Land Registration.